Child-Centered Design: Developing an Inclusive Letter Writing App - Martens, Marianne; Rinnert, Gretchen Caldwell; Andersen, Christine (Frontiers in Psychology, 2018)
Everywhere there are children, there are screens, and child-computer interaction is ubiquitous. Despite their omnipresence, research on the impact of screens on children’s learning, lags behind the development of digital tools. Apple’s App Store has an abundance of “educational” apps, but many of these app’s claims are unsubstantiated. Organizations responsible for vetting quality products for young people, such as the American Library Association, are developing resources to help identify the best digital products available, but they remain difficult to find, and there is limited guidance for app designers when it comes to designing apps for younger audiences. Our interdisciplinary, empirical study was inspired by ‘co-design’ (Sanders and Stappers, 2008) and ‘co-operative inquiry’ (Druin, 2005). Starting with a seed grant from *[Removed for peer Review] College of Communication and Information, our team sought to create a high-quality and inclusive alphabet app with haptic interactions and meaningful gamification (Nicholson, 2012) to reinforce the basic letter writing skills of young children. The app rewards a child’s successful handwriting with an animation of a verb that corresponds with the letter they traced. Concrete animations and digital and verbal demonstrations connect the typographic letter to the handwritten counterpart. Librarian Claudia Haines’ rubric guided our definition of “quality” (Haines, 2016), and children served as co-designers in two qualitative user studies. Our young designers tested prototypes, completed task booklets, and were interviewed about their preferences and their feedback informed our design. Additionally, a focus group interview with kindergarten and preschool teachers provided further feedback about the typographic design, stroke order, and gaming rewards. To be inclusive, children in both our app design and user studies were selected from a diverse pool. Our research contributes to work on co-design and cooperative inquiry in the fields of User Experience Design, human computer interaction, human information behavior, information science, interface design, motion design, typeface design and typography for children, and early literacy development. A post study is planned upon completion of the app.